Evaluation of the results of pulse oximetry screening for detection congenital heart disease in Konya region, Turkey; Is it cost effective? (Annals of Medical Research, 2021)
Aim: Congenital heart disease (CHD) is one of the most common congenital anomalies. It is known that early detection of the critical lesions without symtomatic improves the prognosis of patients in the long term. In our study, we aimed to evaluate the efficacy and cost of pulse oximetry screening for detection of CHD in Konya region.Material and Methods: In our study, we analyzed the results of pulse oximetry screening of infants born between 2016 and 2018 in Selcuk University and Saglik Bilimleri University Konya Training and Research Hospital. Positive screening test results and their costs was evaluated.Results: Pulse oximetry was performed on a total of 3440 infants for screening congenital heart disease at two different centers. 2003 (58.2%) of the cases were female and 1437 (41.8%) were male. The mean timing of screening was 24.7±13.1 (4-100) hours (mean ± SD (min-max). 292 (8.48%) infants were tested positive. Echocardiographic examination was performed in the positive cases. The prevalence of CHD was found to be 27.6 ‰. The prevalence of critical CHD was 1.16 per 1000 live births. The false-positive screen rate was found to be 197 (5.7%). Among the cases who were screened, the most common CHD was the secundum ASD. The total cost of probes was 2622 ₺ ($497.91). The cost of echocardiography for 292 babies was approximately 13181 ₺ ($2503).Conclusion: Screening for heart disease can be used effectively in the early diagnosis of serious and life-threatening diseases in newborn and the cost is unneglectable in the early screening of patients. This study, the total cost of each infant screening is approximately 4.5 ₺ ($0.85) which appears to be a quite cheap and effective screening compared to the other countries.Keywords: Newborn; congenital heart disease; pulse oximetry screening; cardiovascular disease.
Keywords: Newborn; congenital heart disease; pulse oximetry screening; cardiovascular disease.